Students’ critical thinking as an aspect of informational and psychological safety of a person (The Journal of Psychology and Sociology, 2017)
This article presents the study results on students’ critical thinking as an aspect of information-psychological security of personality. The research urgency is caused by a rapid development of computer technology as well as by an increase in global information flows. There is an aggravating impact on the conscious and unconscious components of the individual psyche due to low level of information culture among common population (G.V. Grachev, I.K. Melnik, V.I. Ilyukhin, V. N. Lopatin, G.V. Emelyanov.) Information-psychological security of a person means the protection of individual’s vital interests in the information sphere, as well as personal awareness of its negative influence and resistance mechanisms development. The main purpose of this study is the students’ critical thinking as an important part of personal informationpsychological security. Critical thinking is the kind of thinking that helps to critically evaluate any claims without merely taking everything on faith without evidence, but at the same time it helps to stay open to new ideas and methods. Critical thinking is a necessary condition for freedom of choice, the quality of the forecast, the responsibility for your own decisions. A comparison of critical thinking gives the possibility to consider it a determining factor of personal psychological security information level. Further development of critical thinking will help to optimize process future specialists’ professional training in higher education sphere and raise psychological information security level of a person as a whole.Key words: information-psychological safety criteria for information and psychological security, critical thinking, psychological awareness.